Efficacy of Low Daily Dose of Tadalafil as Mono-Therapy for Diabetic Patients With Lower Urinary Tract Symptoms Suggestive of Benign Enlargement of Prostate (Bangladesh Journal of Urology, 2020)
Objective: To assess efficacy of tadalafil or tamsulosin versus placebo for LUTS/BEP.Methods: This was a triple blind randomized control trial (RCT). This study was done on 150 cases of well controlled diabetic patients with LUTS/BEP after screening. The patients were >45 years of age, international prostate symptom score (IPSS) > 13, maximum urine flow rate (Qmax) 10-15 ml/sec. Selected patients were randomized in to 1:1:1 ratio to once-daily tadalafil 5 mg, tamsulosin 0.4 mg, or placebo for 12 weeks. Efficacy measures were assessed by IPSS, Qmax, post-voidal residue (PVR) in ultra-sonogram.Results: IPSS significantly improved versus placebo through 12 wk with tadalafil (-4.81; p